Optimal prestress design of composite cable-stayed bridges. (1st June 2017) - Fabbrocino, F.; Modano, M.; Farina, I.; Carpentieri, G.; Fraternali, F.
Abstract: The present study considers the optimal pre-tensioning design of lattice structures forming composite cable-stayed bridges. With reference to a model problem, a target bending moment distribution over the longitudinal beams is identified, with the aim of achieving an optimized use of the material composing the bridge. Next, a procedure for the optimization of cable forces is developed, in order to achieve the desired bending moment distribution through the application of a self-equilibrated state of stress induced by optimal cable pre-tensioning. Results indicate that the given design approach is suitable for the optimization of the pre-tensioning sequence of arbitrary composite cable-stayed bridges.